2000
DOI: 10.1291/hypres.23.625
|View full text |Cite
|
Sign up to set email alerts
|

Lisinopril Reduces Left Ventricular Hypertrophy and Cardiac Polyamine Concentrations without a Reduction in Left Ventricular Wall Stress in Transgenic Tsukuba Hypertensive Mice.

Abstract: This experiment was designed to determine how the angiotensin-converting enzyme inhibitor, lisinopril, acts on left ventricular wall stress and cardiac polyamine concentrations in Tsukuba hypertensive mice (THMs) carrying both human renin and angiotensinogen genes. Twelve-week-old THMs were treated with either lisinopril or hydralazine, or were left untreated, for 8 weeks. C57BL/6 mice of similar age were used as normal controls. Each group consisted of 14 mice. The systolic blood pressure of each mouse was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…It has been reported that there is a close relationship between wall stress and cardiac hypertrophy (21). However, Kai and Ishikawa has reported that lisinopril reversed cardiac remodeling without a reduction in LV wall stress in transgenic hyprertensive mice (22). This report supports our present results.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that there is a close relationship between wall stress and cardiac hypertrophy (21). However, Kai and Ishikawa has reported that lisinopril reversed cardiac remodeling without a reduction in LV wall stress in transgenic hyprertensive mice (22). This report supports our present results.…”
Section: Discussionsupporting
confidence: 91%
“… 37 The serum concentration of AngII is 4 to 5 times higher in THM than in the C57BL/6 mice. 38 , 39 Because nutrition of articular cartilage is provided by diffusion from vessels in subchondral bone and bone marrow and percolation through synovial fluid, 40 it is possible that the high serum AngII concentration upregulated the AT1R in chondrocytes in articular cartilage. Together, the mechanical stresses induced by forced running and higher serum and cartilage concentrations of AngII in the THM might have resulted in synergistic upregulation of AT1R expression.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, a direct comparison of hydralazine and lisinopril at doses that lower blood pressure equally also shows additional effects of ACE inhibitors unrelated to blood pressure effects. 12 In another study, Kauser et al 13 reported that apoE KO mice treated with L-N-arginine methyl ester (L-NAME) at doses that do not raise blood pressure still have increased lesion areas. These results agree with ours in that the predominant effect of NOS inhibition on atherogenesis seems independent of blood pressure.…”
Section: Discussionmentioning
confidence: 99%